2017
DOI: 10.1111/cas.13348
|View full text |Cite
|
Sign up to set email alerts
|

CENP‐R acts bilaterally as a tumor suppressor and as an oncogene in the two‐stage skin carcinogenesis model

Abstract: CENP‐R is a component of the CENP‐O complex, including CENP‐O, CENP‐P, CENP‐Q, CENP‐R, and CENP‐U and is constitutively localized to kinetochores throughout the cell cycle in vertebrates. CENP‐R‐deficient chicken DT40 cells are viable and show a very minor effect on mitosis. To investigate the functional roles of CENP‐R in vivo, we generated CENP‐R‐deficient mice (Cenp‐r −/−). Mice heterozygous or homozygous for Cenp‐r null mutation are viable and healthy, with no apparent defect in growth and morphology, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Our previous study demonstrated the essential function of Cenp‐r in the two‐stage skin carcinogenesis model 23 . In this study, our expression analysis suggested that Cenp‐50/U functions might be opposite to those of Cenp‐r in skin carcinogenesis (Figure 1).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Our previous study demonstrated the essential function of Cenp‐r in the two‐stage skin carcinogenesis model 23 . In this study, our expression analysis suggested that Cenp‐50/U functions might be opposite to those of Cenp‐r in skin carcinogenesis (Figure 1).…”
Section: Resultssupporting
confidence: 54%
“…This finding suggests that Cenp‐50/U functions as an oncogene in papilloma development, but loses this function at the late papilloma stage and in malignant conversion. We previously reported that Cenp‐r deficiency increases early‐stage papillomas and reduces the conversion of benign papillomas into malignant tumors 23 . These results suggest that Cenp‐50/U functions as an oncogene, whereas Cenp‐r functions as a tumor suppressor in early papilloma development.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Since the AhR ligands, FICZ, and DMBA, are reported to promote carcinogenesis in SCC ( 11 ), we firstly employed immunohistochemical staining of CYP1A1 and AhR in 10 cases in each condition (cutaneous SCC, AK, and normal skin). Atypical keratinocytes in AK ( Figures 1A,B ) and cutaneous SCC ( Figures 1C,D ) expressed CYP1A1, whereas normal keratinocytes between the follicular bulbs in AK ( Figure 1A ), surgical margin of cutaneous SCC ( Figure 1E ), or normal skin ( Figure 1F ) did not express CYP1A1.…”
Section: Resultsmentioning
confidence: 99%
“…7,12-Dimethylbenz[a]anthracene (DMBA), another type of AhR ligand that is typically found in cigarette smoke, is widely known to induce cutaneous SCC in mouse skin together with 12-O-Tetradecanoylphorbol 13-acetate (TPA) ( 11 , 12 ). The majority of DMBA-induced SCCs possess mutations in oncogenes including Hras, Kras, and Rras ( 13 , 14 ), which are detected in human SCC located in cervical, esophageal, and lung tissues, among others.…”
Section: Introductionmentioning
confidence: 99%